Investigation of cost saving with common components in a product family - En, Pei Qing (Nanyang Technological University, 2023)
Component commonality is a critical concept in modern manufacturing, as it has been demonstrated to offer several benefits, such as lower inventory costs, reduced lead time, and increased production flexibility. This paper provides an overview of the concept of 12 different types of component commonality indices. Each index focuses on different aspects of commonality and can be useful for engineers to identify which components can be shared among product families.